(untitled) (Dhaka University Journal of Biological Sciences, 2021)
The ability of E. coli to form complex surface-associated communities, called biofilms, contribute to its resistance and persistence in Urinary Tract Infection (UTI). In the present study, the ability of uropathogenic E. coli (n=30) isolated from UTI patients to form biofilm and the concentration of Azithromycin to inhibit or kill planktonic and biofilm phase bacteria were investigated. Effects of sub-Minimum Inhibitory Concentration (MIC) of Azithromycin on biofilm formation was investigated. An attempt was also taken to identify the quorum sensing molecule released by E. coli in biofilm. Among the 30 isolates, 6 (20%) were very strong, 8 (26.67%) were strong, 13 (43.33%) were moderate and 3 (10%) were weak biofilm producers. MIC and MBC (Minimum bactericidal concentration) of planktonic phase bacteria were determined and compared with MRC (Minimum regrowth concentration) and MBEC (Minimum biofilm eradication concentration) of biofilm population. MIC values ranged between 0.5 μg/ml to greater than 512 μg/ml. MBC values were measured for ten isolates and the range found was between 8-64 μg/ml. It was found that MRC values were 2-256 times greater than MIC values and MBEC values were 16-256 times greater than corresponding MBC values. After subjecting sub MIC Azithromycin levels to 10 selected isolates, 6 lost the ability to form curli fimbriae and 2 lost their capability of motility in planktonic stage, but none of this ability was lost in biofilm stage. Viable cell count of planktonic cells incubated in sub MIC Azithromycin concentration showed significant decrease of cell number whereas the number of planktonic cells without antibiotic increased significantly. In contrast, for biofilm forming cells, no change in cell number was seen with progressing time for either the presence or absence of antibiotic indicating that biofilm formation could not be inhibited by sub MIC concentrations of Azithromycin. It can be implied that Azithromycin is not the proper drug of choice for eradication of biofilm formed by E. coli. The present study failed to identify the quorum sensing molecule released by the test isolates by the method employed. Dhaka Univ. J. Biol. Sci. 30(1): 1-11, 2021 (January)